Demographic Differences in the Work-Family Conflict and Health Status among Married Civil Servants in Ebonyi State, Nigeria - Nwamaka Agbe Elom; Cajetan Ikechukwu Ilo; Nwimo, Ignatius Obilor; Jude Ifeanyi Nkwoka; Rita Ngozi Ojide; Anthonia Ezugwu Uchechukwu; Lazarus Eneje Ezugwu (Archives of Business Research, 2019)
Using cross-sectional survey, the study described demographic differences in work-family conflict (WFC) and health status (HS) among 737 married civil servants. Work-family Conflict Scale (WFCS) and a self-developed Health Status Scale (HSC) were used to collect data. Results showed females had higher WFC than males; younger ones (18-40 years) had higher WFC than older ones; those with qualifications below SSCE had higher WFC than those with SSCE and above; and junior workers had higher WFC than seniors. The reverse was the case in relation to health status. All the differences in WFC and HS were significant with regard to demographic variables studied. The findings of this study seemed to suggest a relationship between WFC and HS, implying that the higher ones WFC, the lower the HS of the individual. The study concluded that high level of WFC experienced by the subjects might have contributed to their low health status. Health promotion in the workplace should be a top priority of government since workers’ health determines their ability to work effectively in any organization.